Priming effects on safety decisions in a virtual construction simulator. Issue 2 (19th March 2018) - Lu, Xueqing; Davis, Steven
Abstract : Purpose: The purpose of this paper is to investigate the influence of priming on people's risk perceptions and safety decisions in a virtual construction simulator. Design/methodology/approach: Civil engineering students were recruited to interact with a virtual reality (VR) safety simulator. They were divided into four groups covering with and without sound and with and without priming factors. Data were collected on the risks that they perceived and the safety levels of their actions. Findings: It was found that obvious stimuli in a virtual environment with sound help people to recognise more hazards near the location of the stimuli. Sound is helpful in training simulations to create high levels of presence. However, priming factors are not suitable to be added to VR simulators for training purposes. Priming of safe choice results in people taking fewer risks in the VR simulator, but this does not carry over into other situations. Compared to priming effects, being "injured" in a training simulator with sound improves trainees' ability to make safe decisions. Originality/value: VR simulation is helpful in construction training because of its unique ability to give trainees exposure to dangerous situations without physical risk. However, the overloading the working memory of users is detrimental to the outcomes. Therefore, the optimum level of complexity in VR simulators should be further studied.